Shocks, sensitivity and resilience: tracking the economic impacts of environmental disaster on assets in Ethiopia and Honduras - Carter, Michael R.; Little, Peter D.; Mogues, Tewodaj; Negatu, Workneh (International Food Policy Research Institute, 2006)
Droughts, hurricanes and other environmental shocks punctuate the lives of poor and vulnerable populations in many parts of the world. The direct impacts can be horrific, but what are the longer-term effects of such shocks on households and their livelihoods? Under what circumstances, and for what types of households, will shocks push households into poverty traps from which recovery is not possible? In an effort to answer these questions, this paper analyses the asset dynamics of Ethiopian and Honduran households in the wake of severe environmental shocks. While the patterns are different across countries, both reveal worlds in which the poorest households struggle most with shocks, adopting coping strategies which are costly in terms of both short term and long term well-being. There is some evidence that shocks threaten long term poverty traps and that they tend to militate against any tendency of the poor to catch up with wealthier households. Policy implications are discussed in terms of access to markets and the design of government safety net programs.